Concept of Short-Range Radar and Counter-Projectilef or Detecting and Countering Armour-Piercing Projectiles - Adam RUTKOWSKI (Koncepcja radaru bliskiego zasięgu oraz antypocisku do wykrywania i zwalczania pocisków przeciwpancernych, 2021)
During warfare and acts of terrorism an extreme threat to vehicles and other high-value assets comes from armour-piercing projectiles. Under these conditions, defence systems should include devices capable of rapid detection of these threats. Defence assets should also be provided with counter-projectile systems capable of destroying incoming armour-piercing projectiles at a safe distance from the asset to be protected. This paper describes the concept of a system comprising of a lightweight shortrange radar and a counter-projectile for countering armour-piercing projectiles. The purpose of the radar is to monitor the environment and search for incoming armour-piercing projectiles. When an armour-piercing projectile is detected in a designated monitoring area, an automatic command is given for the counter-projectile launcher to be fired. The counter-projectile deployed can be equipped with a single or multi-sensor detection head unit and an explosive payload module, both being the primary components of the warhead. When the signal analysis blocks interfaced with the detection head determine that the armour-piercing projectile to be struck down is in the target position in relation to the counter-projectile deployed, they automatically command the explosive payload module to detonate. The components of the system concept were tested in proving ground conditions. The successful results of these tests confirmed the validity of the solutions initially adopted and the execution of the individual systems.
Keywords: Wykrywanie i zwalczanie pocisków przeciwpancernych